2017
DOI: 10.1016/j.immuni.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Brain Ischemia Suppresses Immunity in the Periphery and Brain via Different Neurogenic Innervations

Abstract: Brain ischemia inhibits immune function systemically, with resulting infectious complications. Whether in stroke different immune alterations occur in brain and periphery and whether analogous mechanisms operate in these compartments remains unclear. Here we show that in patients with ischemic stroke and in mice subjected to middle cerebral artery occlusion, natural killer (NK) cells display remarkably distinct temporal and transcriptome profiles in the brain as compared to the periphery. The activation of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
154
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 54 publications
12
154
1
3
Order By: Relevance
“…Patients suffered from ischemic stroke exhibit marked reduced spleen size and circulating NK cell numbers during acute phase of stroke onset, and these phenomena are also observed in MCAO mice [35]. In line with these findings, the present study also observed a slight decrease in the percentage of NK cells of lymphocytes in both spleen and circulating blood.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients suffered from ischemic stroke exhibit marked reduced spleen size and circulating NK cell numbers during acute phase of stroke onset, and these phenomena are also observed in MCAO mice [35]. In line with these findings, the present study also observed a slight decrease in the percentage of NK cells of lymphocytes in both spleen and circulating blood.…”
Section: Discussionsupporting
confidence: 90%
“…In line with these findings, the present study also observed a slight decrease in the percentage of NK cells of lymphocytes in both spleen and circulating blood. Brain ischemia activates catecholaminergic and hypothalamicpituitary-adrenal (HPA) axis, which leads to immunity suppression in the periphery [35]. It is noteworthy that BHD treatment did not affect the NK cell levels in either the spleen or blood following brain ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that despite its potential function in bacterial defense, the number of NK cell population might not be a good indicator for stroke severity or functional deficits. Interestingly, a recent preclinical study suggested that brain ischemia could result in impaired NK cell-mediated immune defense through distinct mechanisms in the brain vs in the periphery and could therefore be differentially regulated to limit poststroke inflammation 6. In this case, the different effects of central and peripheral NK cells on stroke outcomes should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Such lymphopenia can last for months with a gradual recovery over time. Multiple mechanisms, including the activation of sympathetic nervous system,3 the dysregulation of hypothalamic–pituitary–adrenal axis,6,7 and the release of danger-associated molecular patterns from injured brain,8 have been suggested to contribute to these immune changes after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Infarct size of the ischemic stroke model was assessed with a 7 T small animal MRI previously described (Bruker Daltonics Inc., Billerica, MA, USA) (9, 27, 31). During scans, mice were placed on a regulated‐heated blanket (Bruker Daltonics Inc.) to maintain body temperature at 37.0 ± 0.5°C.…”
Section: Methodsmentioning
confidence: 99%